KUALITAS DAN DESAIN PRODUK DALAM MENINGKATKAN KEPUASAN DAN LOYALITAS KONSUMEN (Studi Kasus Baju Dagadu Yogyakarta) - Dani Haris (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
This study aims to analyze the effect of product quality and product design with intervening variables, dagadu products In YogyatouriumYogyakarta. The result of the research is the first hypothesis rejected. The second hypothesis is rejected. The third hypothesis is rejected. The fourth hypothesis is accepted. The Fifth Hypothesis is rejected. The sixth hypothesis is rejected. The seventh hypothesis is accepted. The conclusion in this research are: 1) product quality has negative and insignificant effect to customer satisfaction; 2). Product design has no significant positive effect on customer satisfaction; 3) Product Quality has negative and insignificant effect to consumer loyalty; 4) Product Descriptions have a positive and significant impact on consumer loyalty; 5) Consumer Satisfaction has a positive influence on the consumer loyalty; 6) The effect of product quality with satisfaction as intervening variable is not able to give positive and significant influence to the increase of consumer loyalty; 7) The effect of product design with satisfaction as intervening variable can give positive and significant influence to the increase of consumer loyalty.